MANAJEMEN BENCANA OLEH BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM MENANGGULANGI BANJIR DI KOTA SEMARANG - Dio Mahardika; Endang Larasati Setianingsih (Journal of Public Policy and Management Review, 2018)
The most frequent disaster in many city of Indonesia is flood disaster, so disaster management is required to minimize the risks caused by floods. This study focuses on disaster management conducted by the Regional Disaster Management Agency (BPBD) Semarang City, whether it is in accordance with the stages of disaster management that is pre-disaster, during the disaster, and post disaster. So this research is to find out how the disaster management conducted by Regional Disaster Management Agency (BPBD) Semarang City in handling the flood disaster. The research method used in this research is qualitative method of descriptive type, with staff as an informant from Regional Disaster Management Agency (BPBD) Semarang City which has duty to conduct disaster management in Semarang City. This research explains about how disaster management conducted by BPBD in tackling flood disaster in Semarang City is in accordance with disaster management theory or not yet. The results showed that the stages of disaster management carried out BPBD Semarang City is starting from pre-disaster that there are still shortcomings that is not the formation of contingency plans, then in the stage when there is a disaster that is lack of logistics and disaster emergency personnel, and the last stage is post-disaster there are still shortcomings where the form of rehabilitation conducted BPBD there are still less appropriate target.